Profile of Elementary School Teacher Candidates' Understanding of the STEAM Approach - Purnamasari, Veryliana; Handoyo, Eko; Yulianto, Arief; Isdaryanti, Barokah (Proceedings of International Conference on Science, Education, and Technology, 2024)
The background that drives this research is that as the times develop, new literacy is needed in the world of education to improve the quality and quality of education by introducing teachers to the STEAM approach. The focus of the problem in this study is how the profile of the understanding of prospective elementary school teachers towards the STEAM (Science, Technology, Engineering, Arts, and Mathematics) approach in Semarang City. This type of research is qualitative descriptive. Data collection in this study was carried out by methods of (1) observation, (2) interviews, (3) questionnaires, and documentation. The subject of this study is prospective elementary school teachers in the city of Semarang. The sample taken was students who were studying for the Pre-service Teacher Profession in Semarang City. The data obtained from the results of interviews with teachers, students, and parents were processed using data triangulation. This study concludes that not all students of Pre-service teacher professional education know about the STEAM (Science, Technology, Engineering, Arts, and, Mathematics) approach, but they have unconsciously implemented or applied the STEAM (Science, Technology, Engineering, Arts, and, Mathematics) approaching the learning process. This can be proven by the existence of prospective teachers who can give student assignments in the form of projects.